Bis-chelated-(3-methoxy-2-oxo-benzaldehyde)–copper(II) complex: Synthesis, crystal structure, fluorescence property, DFT calculation, and catecholase activity. (9th March 2015) - Mistri, Soumen; Bertolasi, Valerio; Manna, Subal Chandra
Graphical abstract: Bis-chelated-(3-methoxy-2-oxo-benzaldehyde)–copper(II) compound was synthesized and characterized by crystal structure and DFT/TD-DFT calculation. The electronic spectrum and IR spectrum of compound was compared with result obtained by employing DFT and TD-DFT calculation. The compound shows catecholase activity and intense fluorescence at room temperature. Abstract: Reaction of Cu(NO3 )2 ·3H2 O and 2-hydroxy-3-methoxybenzaldehyde (HL) in methanolic medium results [CuL2 ]·4H2 O (1 ) [L −  = 3-methoxy-2-oxo-benzaldehyde]. The complex was characterized by elemental analysis, IR, single crystal X-ray structure determination and DFT calculation. The X-ray single crystal structure determination reveals that1 is a discrete mononuclear four coordinated complex with the metal in square planar coordination geometry and four lattice water molecules. The complex form dimer around the center of symmetry with short Cu⋯O interaction and exhibits intense fluorescence ( λ ex  = 270 nm, λ em  = 311, 328, 355 and 367 nm) in methanolic solution at room temperature with a fluorescence quantum yield Φs  = 3.5. The complex1 was tested with several aromatic compounds such as m -toluidine, aniline, nitrobenzene and o -nitrotoluene, and the results show that a pronounced fluorescence quenching and enhancement is observed in the presence of nitrobenzene and m -toluidine, respectively. Catecholase activity of1 has been investigated in methanol medium by UV–Vis spectrophotometric study using 3, 5-di- tert -butylcatechol (3, 5-DTBC) as model substrate reveals that1 is active for catalyzing aerobic oxidation of 3, 5-di- tert -butylcatechol to 3, 5-di- tert -butylbenzoquinone (3, 5-DTBQ). The optimized geometry from density functional theory (DFT) study shows a good agreement with X-ray structural data. The electronic and IR spectrum of this compound is compared with result obtained by employing DFT and time dependent density functional theory (TD-DFT) calculation.